2011
DOI: 10.1590/s1516-35982011000900030
|View full text |Cite
|
Sign up to set email alerts
|

Resultados econômicos da produção de cordeiros em confinamento utilizando na dieta casca de soja associada a quatro fontes de nitrogênio não-proteico

Abstract: RESUMO -O objetivo neste estudo foi avaliar o custo de produção e a resposta econômica da utilização de casca de soja (CS) associada a duas fontes de nitrogênio não-proteico (NNP) na terminação de cordeiros em confinamento. Foram utilizados 80 cordeiros mestiços Suffolk, com idade inicial de 69 ± 6 dias e peso vivo inicial de 23,11 ± 1,78 kg. Os animais foram distribuídos em quatro grupos, cada um com uma dieta formulada com uma fonte de NNP: grupo ureia convencional, na proporção de 1%; grupo ureia protegida,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Silva et al (2010) also offered detoxified castor meal to finishing sheep, but for a short period of time, and observed blood urea within the normal physiological limits for the species. Ziguer et al (2012) also observed normal albumin levels in sheep fed soybean hulls for 47 days.…”
Section: Discussionmentioning
confidence: 61%
“…Silva et al (2010) also offered detoxified castor meal to finishing sheep, but for a short period of time, and observed blood urea within the normal physiological limits for the species. Ziguer et al (2012) also observed normal albumin levels in sheep fed soybean hulls for 47 days.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies also showed no effect of increasing levels of urea in the diet on the ADG and FCR in lambs (OKAMOTO et al, 2008;ZIGUER et al, 2012). Mean values for ADG, FCR and GFE were 0.225 kg day -1 , 5.33 kg DM kg gain -1 and 0.195 kg gain kg DM -1 , respectively.…”
Section: Resultsmentioning
confidence: 87%
“…The serum urea showed relationship inversely proportional to the concentrate supplementation levels, although there was no difference (P>0.05) between treatments (Ziguer et al, 2012). When breed effect was evaluated, higher values were found for SI ewes (P<0.05).…”
Section: Effects Of Supplementation In Native Ewesmentioning
confidence: 80%